2015
DOI: 10.1038/mi.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

Novel chimpanzee adenovirus-vectored respiratory mucosal tuberculosis vaccine: overcoming local anti-human adenovirus immunity for potent TB protection

Abstract: Pulmonary tuberculosis (TB) remains to be a major global health problem despite many decades of parenteral use of Bacillus Calmette-Guérin (BCG) vaccine. Developing safe and effective respiratory mucosal TB vaccines represents a unique challenge. Over the past decade or so, the human serotype 5 adenovirus (AdHu5)-based TB vaccine has emerged as one of the most promising candidates based on a plethora of preclinical and early clinical studies. However, anti-AdHu5 immunity widely present in the lung of humans po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 64 publications
3
46
0
1
Order By: Relevance
“…Whilst it is recognised that neither IV nor IT BCG delivery strategies are appropriate for deployment in the clinical setting, recent NHP vaccine evaluation studies and early stage clinical trials have demonstrated that alternative vaccination strategies such as aerosol delivery are a practical, safe and immunogenic approach for the delivery of TB vaccines [43], [44], [57], [58], [59], [60]. The identification of IV-delivered BCG as a highly protective vaccination strategy may prove a pivotal step towards deciphering protective immunological mechanisms against M. tb infection in pre-clinical models, potentially leading to the identification of immune correlates of protection, which could be used to accelerate the vaccine development pipeline.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it is recognised that neither IV nor IT BCG delivery strategies are appropriate for deployment in the clinical setting, recent NHP vaccine evaluation studies and early stage clinical trials have demonstrated that alternative vaccination strategies such as aerosol delivery are a practical, safe and immunogenic approach for the delivery of TB vaccines [43], [44], [57], [58], [59], [60]. The identification of IV-delivered BCG as a highly protective vaccination strategy may prove a pivotal step towards deciphering protective immunological mechanisms against M. tb infection in pre-clinical models, potentially leading to the identification of immune correlates of protection, which could be used to accelerate the vaccine development pipeline.…”
Section: Resultsmentioning
confidence: 99%
“…For intracellular cytokine staining cells were cultured in the presence of GolgiPlug (5 mg/ml brefeldin A; BD Pharmingen) with or without stimulation for 5-6 h with an Ag85Aspecific CD8 T cell-specific peptide (MPVGGQSSF) as previously described (11,31,32) at a concentration of 1 mg per well. In some experiments lung mononuclear cells were stimulated with crude bacillus Calmette-Guérin and M. tuberculosis culture filtrate Ags at a concentration of 1 mg per well of each stimuli (34). The cytotoxicity of CD8 T cells was evaluated by adding CD107a-FITC during the period of Ag stimulation (32).…”
Section: Tetramer and Ag Stimulation Intracellular Cytokine Stainingmentioning
confidence: 99%
“…Virusni vektori mogu da se koriste za zaštitu od različitih infektivnih bolesti, npr. protiv onih koji su izazvani protozoama (malarija) (33), mikobakterijama (tuberkuloza) (34,35) ili virusima (HIV, Denga virus) (36,37). Od virusnih vektora najčešće se primenjuju adenovirusni vektori, za koje je pokazano da indukuju izuzetno snažan CD8+ T ćelijski odgovor kao i produkciju antitela (38).…”
Section: Mehanizam Delovanja Vektorskih Vakcinaunclassified